Foreign Aid, IFRS Adoption and Foreign Direct Investment - Uchenna Efobi; Matthias Nnadi (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The attraction of Foreign Direct Investment (FDI) is arguably of particular importance to countries' foreign policy, where competing factors determine the choice of location of these investors. IFRS adoption, being one of the cardinal frameworks that portray the quality of a countries information environment, is seen as having a significant influence on the choice of FDI location. Noting that foreign aid (a form of foreign finance) may compete directly with, or complement FDI, this paper investigates the extent to which IFRS adoption is able to at-tract FDI in the presence of this form of finance. The main idea being that the effect of IFRS adoption on FDI may be adjustable depending on the presence of, and the kind of foreign aid flow in the country. Using a panel data of 92 countries for the period 2003-2012, we indeed find that IFRS adoption attracts more FDI, conditioned on foreign aid; however, when dis-aggregating foreign aid, the effect of bilateral aid was contradictory, while multilateral aid flow was positive. This result remained consistent despite the battery of checks.
Additional information: This is a working paper and comments are welcomed.
Keywords: 330; Accounting Standards; Foreign Aid; Foreign Direct Investment; Globalisation; IFRS Adoption